Aschizomys lemminus - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
63. Lemming Mountain Vole Aschizomys lemminus French: Campagnol lemming / German: Lemming-Gebirgswiihimaus / Spanish: Topillo de montana lemming Other common names: Lemming Vole Taxonomy. Aschizomys lemminus G. S. Miller, 1899, “Kelsey Station, Plover Bay, Bering Strait, [Chukotskiy], Siberia [Russia].” In the past, A. lemminus was frequently classified as a species of Alticola or a subspecies of Myodes macrotis (as Alticola macrotis or Aschizomys macrotis). Monotypic. Distribution. E Siberia and Russian Far East (E of Lena River and Yablonoi Mts E to Chukchi Peninsula). Descriptive notes. Head-body 88- 120 mm,tail 10-28 mm; weight 21-39 g. Lemming Mountain Vole is small relative to species of Alticola. Tail is 16-24% of head-body length, is densely covered with hair, and has distinct tuft; it is distinctly bicolor, blackish brown above and gray below. Summer pelage is ash gray washed brown, belly is whitish gray, and demarcation on flanks is distinct. In most populations, winter pelage is whitish, washed cream, brownish on head. Northern populations are whiter than southern populations. Spring molt occurs from April to early July, autumn molt in September—October. Skull is small, semi-circular, and delicate. Molars resemble condition in Myodes rather than in Alticola. Enamelis thick, accumulation of cement is modest, and angles are rounded. Molars are hypsodont and rootless. Habitat. Accumulations of rocks and talus slopes covered by mosses and lichens and surrounded by grasses, sage (Artemisia, Asteraceae), and shrubs from sea level to elevations of ¢.2000 m. Rocks of moderate size are preferred over large boulders or small stones. Food and Feeding. Diet mainly contains lichens (Cetraria, Parmelia, Thamnolia, Alectoria, and Cladonia), followed by (in declining importance) mosses, berries (Rubus, Rosaceae and Vaccinium, Ericaceae), leaves, flowers and grass seeds, pine seeds, invertebrates and fruits. In Yakutia (= Sakha Republic), no less than 59 flowering plants were identified in the diet. Most frequently ...